ANALISIS KONFLIK BATIN TOKOH DALAM NOVEL ANTARA AKU DAN DIA KARYA AGNES JESSICA: KAJIAN PSIKOLOGI SASTRA SIGMUND FREUD - Siti Mazlin; Elsa Mulya Karlina (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to describe the inner conflict of the main character in the novel Antara Aku dan Dia by Agnes Jessica based on Sigmund Freud's psychoanalytic theory. This study employed a qualitative approach using a descriptive research design. The data consisted of words, sentences, dialogues, and narratives depicting the main character's inner conflict. Data were collected through reading and note-taking techniques and analyzed using the Miles and Huberman data analysis model. The findings reveal that the main character's inner conflict is reflected in the three structures of personality: id, ego, and superego. In addition, the study identifies several forms of inner conflict, including fear, anxiety, hesitation, guilt, and courage. The findings indicate that inner conflict influences the main character's attitudes and decision-making in dealing with various life problems.